STRATEGI PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN PRODUK DI GIVIE DESSERT - Azaria, Safhira; Fachrurrazi, Fachrurrazi; Atika, Nur (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2023)
Safhira Azaria (11725046), “Marketing Strategy to Increase Sales Volume at Givie Dessert”. Faculty of Islamic Economics and Business Islamic Business Management Study Program, State Islamic Institute (IAIN) Pontianak, 2021. The purpose of this study was to find out what strategy was used and how the implementation of that strategy was used by Givie Dessert in increasing sales volume. With a research focus on marketing strategies to increase sales volume at Givie Dessert. This study used qualitative research methods. Sources of primary data in the form of direct observations and interviews with sources, namely the manager and owner of Givie Dessert. While the data collection technique is by means of observation, interviews, and documentation. Then the data were analyzed using data reduction techniques, data presentation, and drawing conclusions. In the end, the data will be tested for validity using data triangulation and member check techniques. The results of this study indicate that Givie Dessert has implemented a marketing strategy (marketing mix). This has a significant effect on the sales volume of Givie Dessert.